Pelatihan Mengenalkan Struktur Data pada SMK Negeri 2 Cimahi - Tresnawati, Shandy; Ekawati, Nia; Anggreini, Novita Lestari; Rohmayani, Dini (PUAN INDONESIA, 2024)
Data structures and algorithms are important, integrated, and mutually supportive parts of building good and efficient application programs. Paying more attention to this can provide very important results, especially in increasing access speed and providing insight and guidance on how to improve problem solving and find better solutions. The service team conducts community service in Software Engineering expertise, this certainly supports the material that will be delivered to the Software Engineering department about learning Data Structures. In addition, the service team received an explanation from the teacher of SMK Negeri 2 Cimahi, there is data structure learning material so that it is sustainable in the training held by the service team. The material presented by 3 (three) speakers included linked lists, stacks and queues. The following are the results done by the service participants. The conclusion on community service at SMK Negeri 2 Cimahi, the service participants, namely school students, were enthusiastic in learning data structure material. Service participants understand better and can implement the results that have been done in the training process.